2023
DOI: 10.3390/molecules28010392
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiles, In Vitro Antioxidant and Antifungal Activity of Four Different Lavandula angustifolia L. EOs

Abstract: Lavandula angustifolia L., known as lavender, is an economically important Lamiaceae due to the production of essential oils (EOs) for the food, cosmetic, pharmaceutical and medical industries. The purpose of this study was to determine the chemical composition of EOs isolated from four inflorescences of L. angustifolia L. collected in different geographical areas: central-southern Italy (LaCC, LaPE, LaPS) and southern France (LaPRV). The essential oils, obtained by steam distillation from plants at the full f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
1
4
0
1
Order By: Relevance
“…Linalyl acetate ( 3b , Figure 3 ) has been well documented to have favorable bioactivities. Anticancer properties have been associated with essential oils from Lavandula angustifolia, Lavandula officinalis, Lavandula latifolia , and bergamot [ 40 , 41 , 42 , 43 , 44 ], all of which contain linalyl acetate in concentrations as high as 44%. A study conducted on the lavender essential oils from Lavandula angustifolia demonstrated an IC 50 values of 0.36% ( v / v ) against HaCaT cell line in an MTT assay [ 43 ].…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Linalyl acetate ( 3b , Figure 3 ) has been well documented to have favorable bioactivities. Anticancer properties have been associated with essential oils from Lavandula angustifolia, Lavandula officinalis, Lavandula latifolia , and bergamot [ 40 , 41 , 42 , 43 , 44 ], all of which contain linalyl acetate in concentrations as high as 44%. A study conducted on the lavender essential oils from Lavandula angustifolia demonstrated an IC 50 values of 0.36% ( v / v ) against HaCaT cell line in an MTT assay [ 43 ].…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
“…Anticancer properties have been associated with essential oils from Lavandula angustifolia, Lavandula officinalis, Lavandula latifolia , and bergamot [ 40 , 41 , 42 , 43 , 44 ], all of which contain linalyl acetate in concentrations as high as 44%. A study conducted on the lavender essential oils from Lavandula angustifolia demonstrated an IC 50 values of 0.36% ( v / v ) against HaCaT cell line in an MTT assay [ 43 ]. Additionally, there have been reports of linalyl acetate associated antioxidant activity in essential oils of Salvia sclarea , and Myrtus nivellei , across different regions [ 45 , 46 ].…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
“…angustifolia L., събрани oт централна и южна Италия и Южна Франция, като са изследвани тяхната in vitro противогъбична активност срещу две гъбички, причиняващи бяло гниене (Phanerochaete chrysosporium и Trametes cingulata), както и спрямо Sclerotium rolfsii, Botrytis cinerea и Fusarium verticilloides, които били причина за значителни загуби на реколта в тропическите и субтропичните райони. Резултатите потвърждават чувствителността им към четирите лавандулови масла (Caprari et al, 2023).…”
Section: антимикотични ефектиunclassified
“…The composition and proportions of bioactive ingredients in extracts obtained from lavender raw materials determine its biological functions and potential applications. Due to its proven antibacterial [19], antifungal [20], antioxidant [21], and anti-inflammatory [22] properties, this plant is very popular among both breeders and potential recipients of the raw material. Numerous scientific publications devoted to the chemical analysis of the raw material also demonstrate great interest [23,24].…”
Section: Introductionmentioning
confidence: 99%